Thermodynamic Modeling of the Formation of Chromium Carbides in an Applied Metal Layer - Aleshin, N. P.; Kobernik, N. V.; Pankratov, A. S.; Petrova, V. V. (Russian engineering research, 2020)
The use of chromium carbides to harden surfaced metal that is subject to abrasive wear is considered. With correct hardening of the applied layer, carbide formation extends the working life.